1993
DOI: 10.1002/j.2164-4683.1993.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Victimization by School Bullies: New Research and Future Direction

Abstract: This investigation was designed to replicate recent studies of bullying victims and to extend those findings to younger students. Results tended to replicate earlier studies except that a greater number of young students classified themselves as victims and seemed to experience more trauma.Bullying refers to the physical or psychological abuse of an individual by one or a group of students. Attacks tend to be relatively mild, long-term, and unprovoked Olweus, 1978). Harassment is typically directed toward weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 6 publications
3
25
0
4
Order By: Relevance
“…It is now generally accepted that peer-victimization is a relatively common and frequent experience among children and adolescents [e.g., Garcia and Perez, 1989;Hoover et al, 1993;Lagerspetz et al, 1988;Olweus, 1985;Rigby and Slee, 1991;Slee, 1995;Smith, 1991;Whitney and Smith, 1993]. However, although it is accepted that peervictimization encompasses a number of distinct behaviors, there seems to be little agreement about how best to categorize these behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…It is now generally accepted that peer-victimization is a relatively common and frequent experience among children and adolescents [e.g., Garcia and Perez, 1989;Hoover et al, 1993;Lagerspetz et al, 1988;Olweus, 1985;Rigby and Slee, 1991;Slee, 1995;Smith, 1991;Whitney and Smith, 1993]. However, although it is accepted that peervictimization encompasses a number of distinct behaviors, there seems to be little agreement about how best to categorize these behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the research suggests a lack of consensus on the prevalence of bullying in the US. Figures vary widely dependent upon the definition used, methodology, and the applicable time frame (between 5 and 90% of students reporting they were victims of bullying; see Griffin and Gross 2004); although, some studies have suggested that the US has the highest reported prevalence for bullying in the world (e.g., Berthold and Hoover 2000;Hoover et al 1993). Additionally, bullying tends to be subsumed under broader issues of school violence or aggression in the American literature and little attention is directed toward collecting sound data regarding the specific characteristics of bullying in America.…”
mentioning
confidence: 99%
“…Research has identified bullying as being ongoing, unsolicited, and frequently not physically injurious (Hoover, Oliver, & Thomson, 1993;Olweus, 1993). Essentially, bullying is the process of establishing and maintaining social dominance through overt aggression and doing so in ways that victims are unable to deflect because of their lack of skills, their inability to effectively integrate with peers, or their inability to develop subgroups of peers (C. M. J.…”
mentioning
confidence: 99%